Presence of SARS‐CoV‐2 in plural effusion with COVID‐19 patients - Ataee, Zahra (Clin Case Rep, 2021)
RT‐PCR of OP, NP swabs, is the gold standard test for the diagnosis of COVID‐19. CT scan plays an important role in the diagnostic evaluation of COVID‐19. Both methods increase the tracing disease. Even though pleural involvement has been reported less, it has been observed in significant cases.